THE IMPORTANCE OF REFLECTIVE ATTITUDE IN THE CONDITIONS OF ACADEMIC MOBILITY - Ruziyeva Shokhida (Bright Mind Publishing, 2025)
In the modern education system, academic mobility expands the opportunities for students and professors to exchange international experience. This study analyzes the pedagogical importance of a reflexive attitude in the conditions of academic mobility. The article examines the processes of self-assessment and development of academic mobility participants based on the reflexive approach models of such famous scientists as John Dewey and David Kolb. The results of the study show that a reflexive attitude plays a decisive role in increasing the effectiveness of academic mobility programs and ensuring the personal and professional development of participants.
Keywords: Academic mobility, reflexive attitude, Dewey model, Kolb cycle, experiential learning, self-assessment, international education.